1988
DOI: 10.1210/jcem-67-1-104
|View full text |Cite
|
Sign up to set email alerts
|

Quantitating Genetic and Nongenetic Factors Influencing Androgen Production and Clearance Rates in Men*

Abstract: Both hereditary and nonhereditary factors have a decided influence on plasma sex steroid concentrations in men. We studied the relative contributions of genetic and nongenetic factors on the production rate (PR) and MCR of testosterone and dihydrotestosterone (DHT) and their conversion ratios to other metabolites in monozygotic (MZ; n = 22) and dizygotic (DZ; n = 24) male twins. Zygosity was determined by measurement of 10 blood proteins and enzymes. The kinetic studies were conducted with isotope dilution tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(50 citation statements)
references
References 30 publications
6
44
0
Order By: Relevance
“…They estimated that approximately 26%, 36%, 12%, and 48% of the variance in plasma TESTO, free (unbound) TESTO, DHT, and 3 -DIOL-G were due to genetic factors. In another study, Meikle et al (1988) found that genetic factors explained approximately 96% and 85% of the variance in DHT and TESTO production rate (also in male twins) and approximately 36% and 4% of the variance in DHT and TESTO clearance rates. A heritability of 60% was also reported for TESTO in a Dutch study of male twins (Harris et al 1998).…”
Section: Discussionmentioning
confidence: 96%
“…They estimated that approximately 26%, 36%, 12%, and 48% of the variance in plasma TESTO, free (unbound) TESTO, DHT, and 3 -DIOL-G were due to genetic factors. In another study, Meikle et al (1988) found that genetic factors explained approximately 96% and 85% of the variance in DHT and TESTO production rate (also in male twins) and approximately 36% and 4% of the variance in DHT and TESTO clearance rates. A heritability of 60% was also reported for TESTO in a Dutch study of male twins (Harris et al 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Considering that the normal production of steroids in men is 4-11 mg/day [35,36], the dosage is 10-45 times higher than the natural androgen production. Despite the elevated amount of AAS used, the Participant did not present any acute complications associated with AAS misuse; however, we have no data about past chronic effects, or what happened after the study.…”
Section: Discussionmentioning
confidence: 99%
“…Twin studies have demonstrated that genetic factors account for more than 50% of the variability on male serum gonadotropin, sex steroid, and SHBG levels (25,26). With respect to individual genes, the most extensively studied single genetic variant is the AR exon 1 CAG repeat (23,27).…”
Section: Discussionmentioning
confidence: 99%